2015
DOI: 10.1155/2015/929127
|View full text |Cite
|
Sign up to set email alerts
|

Mediastinal B-Cell Lymphoma Presenting with Jugular-Subclavian Deep Vein Thrombosis as the First Presentation

Abstract: Jugular venous thrombosis infrequently could be secondary to malignancy and has seldom been reported secondary to mediastinal large B-cell lymphomas. The postulated mechanisms are mechanical compression that leads to stagnation of blood in the venous system of the neck and/or an increase in the circulating thrombogenic elements that could cause venous thromboembolism as a paraneoplastic phenomenon. We report the case of a middle aged male presenting with right sided neck pain and arm swelling secondary to ipsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The other known reasons for such an occurrence are otolaryngological infections, soft tissue infections around the neck, intravenous drug abuse, recent head/neck surgery, hypercoagulable states such as protein C or S deficiency, factor V Leiden, deficiency of antithrombin III, polycythemia, and hyperhomocysteinemia. Malignant neck masses may also precipitate IJVT (3). There are reported cases of IJVT secondary to a left upper lobe non-small cell lung cancer [7], a soft tissue infection in the vicinity of the internal jugular vein [8], and a deep neck lipoma [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The other known reasons for such an occurrence are otolaryngological infections, soft tissue infections around the neck, intravenous drug abuse, recent head/neck surgery, hypercoagulable states such as protein C or S deficiency, factor V Leiden, deficiency of antithrombin III, polycythemia, and hyperhomocysteinemia. Malignant neck masses may also precipitate IJVT (3). There are reported cases of IJVT secondary to a left upper lobe non-small cell lung cancer [7], a soft tissue infection in the vicinity of the internal jugular vein [8], and a deep neck lipoma [9].…”
Section: Discussionmentioning
confidence: 99%
“…There are three causes listed in Virchow's law that lead to thrombus formation-damage to blood vessels, a hypercoagulable state, and irregular blood flow. Both mechanical blood vessel compression caused by tumors and the production of thrombogenic substances can result in thrombus formation [ 3 ]. These two are the most likely causes for left IJVT in our patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Eltawansy et al (2015) had found that the malignancy had a causal relationship with deep vein thrombosis which can be secondary to the mechanical stress of the tumor on the venous system draining blood from the affected body part or it can a secondary systemic phenomenon of thrombogenic material released into the circulation from the tumorigenic network. Venous thromboembolism (VTE) is found at autopsy in at least 50% of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…15 He responded well to conservative treatment with warfarin. The prognosis of primary thyroid lymphoma is generally good.…”
mentioning
confidence: 94%